Violence In the Family: Social and Legal Problem (Texas Journal of Multidisciplinary Studies, 2023)
This article examines the phenomenon of domestic violence through the prism of the criminal legislation of the Russian Federation, identifies the types of domestic violence and the reasons for the silence of the fact of domestic violence